Treatment of non‐arthritic pseudoparetic shoulders with irreparable massive rotator cuff tears: arthroscopic procedures yield comparable midterm results to reverse arthroplasty - Fabian Plachel; Paul Siegert; Philipp Moroder; Leo Pauzenberger; Brenda Laky; Werner Anderl; Philipp Heuberer (BMC Musculoskeletal Disorders, 2021)
Abstract Background Irreparable massive rotator cuff tears (IMRCTs) are a well-known cause for functional limitation and difficult to treat. Although several joint-preserving as well as joint-replacing procedures were found to provide pain relief and gain of function, midterm results are scarce, particularly in pseudoparetic shoulder joints unaccompanied by severe osteoarthritis. The purpose of this study was to compare the midterm functional outcomes of arthroscopic procedures to those of reverse total shoulder arthroplasty (RTSA) in pseudoparetic shoulders with IMRCTs unaccompanied by severe osteoarthritis. Methods All patients who underwent either joint-preserving (group A) or joint-replacing (group B) procedures for IMRCT unaccompanied by severe osteoarthritis with a pseudoparetic shoulder function were retrospectively included. Clinical assessment included the Constant Score (CS), the Subjective Shoulder Value (SSV) and the Visual Analog Score (VAS) at baseline and at latest follow-up. Furthermore, the complication and revision rates were assessed. Results Overall, a total 56 patients were included of whom each 28 patients formed group A (male, 36%) and B (male, 53%) with a mean patient age at time of surgery of 70 ± 7 years and 72 ± 7 years, respectively. The mean follow-up period was 56 ± 17 months. At final follow-up, the total CS (group A: 66 ± 14 points; group B 54 ± 15 points) was significantly increased after arthroscopic treatment when compared to RTSA (p=0.011). However, no significant differences were detected with SSV (p=0.583) and VAS (p=0.536). Although complication rate (11% versus 18%) was not significantly different (p=0.705), number of revision surgeries was significantly higher in group B when compared to group A (p=0.041). Conclusions In non-arthritic pseudoparetic shoulders, both joint-preserving and joint-replacing procedures yielded good clinical midterm outcomes for the treatment of degenerative IMRCTs. Despite of comparable functional and satisfactory functional improvement, increased complication rates and surgical invasiveness outweigh the benefits of primary RTSA and therefore reserve this procedure to a second-line treatment in pseudoparetic patients without any signs of severe cuff arthropathy.